Preparation of organic–inorganic hybrid membranes with superior antifouling property by incorporating polymer-modified multiwall carbon nanotubes. Issue 49 (14th June 2017) - Zhu, Kai; Wang, Guibin; Zhang, Shuling; Du, Yinlong; Lu, Yaning; Na, Ruiqi; Mu, Yongfeng; Zhang, Yunhe
Abstract : Schematic illustration of (a) the polymerization of dopamine, and (b) preparation of the PVP-modified MWCNTs. Abstract : Functionalized multiwall carbon nanotubes (MWCNTs) were prepared by coating polyvinylpyrrolidone (PVP) on the MWCNTs surface via multiple hydrogen-bonding interactions between polyvinylpyrrolidone and a mussel-inspired polydopamine (PDA) intermediate. The modified MWCNTs exhibited outstanding dispersity and stability in water and were used as a hydrophilic additive to increase the permeability and antifouling properties of polyethersulfone (PES) ultrafiltration membranes. The results of Fourier transform infrared spectroscopy (FTIR) and X-ray photoelectron spectroscopy (XPS) confirmed the introduction of PDA and PVP into the MWCNTs. The measured water contact angle of the hybrid membranes revealed dramatically enhanced hydrophilicity. The morphology of the hybrid membranes was investigated by field emission scanning electron microscopy (FESEM). Furthermore, the permeability and antifouling properties of the hybrid membranes when mixed with different types and quantities of MWCNTs were compared. The hybrid membrane containing 0.1% PVP-modified MWCNTs exhibited the best overall performance, including a flux recovery ratio as high as 95%. The facile and universal treatment method developed in the present study can be used to improve the comprehensive performance of membranes, with great potential application in wastewater treatment.